Advancing urban wildlife research through a multi‐city collaboration. Issue 4 (1st April 2019) - Magle, Seth B; Fidino, Mason; Lehrer, Elizabeth W; Gallo, Travis; Mulligan, Matthew P; Ríos, María Jazmín; Ahlers, Adam A; Angstmann, Julia; Belaire, Amy; Dugelby, Barbara; Gramza, Ashley; Hartley, Laurel; et al.
Abstract : Research on urban wildlife can help promote coexistence and guide future interactions between humans and wildlife in developed regions, but most such investigations are limited to short‐term, single‐species studies, typically conducted within a single city. This restricted focus prevents scientists from recognizing global patterns and first principles regarding urban wildlife behavior and ecology. To overcome these limitations, we have designed a pioneering research network, the Urban Wildlife Information Network (UWIN), whereby partners collaborate across several cities to systematically collect data to populate long‐term datasets on multiple species in urban areas. Data collected via UWIN support analyses that will enable us to build basic theory related to urban wildlife ecology. An analysis of mammals in seven metropolitan regions suggests that common species are similar across cities, but relative rates of occupancy differ markedly. We ultimately view UWIN as an applied tool that can be used to connect the public to urban nature at a continental scale, and provide information critical to urban planners and landscape architects. Our network therefore has the potential to advance knowledge and to improve the ability to plan and manage cities to support biodiversity.